Baicalin suppress growth and virulence-related factors of methicillin-resistant Staphylococcus aureus in vitro and vivo. (February 2020) - Zhang, Shouping; Hu, Bin; Xu, Jingfei; Ren, Qiuxuan; Wang, Zhichen; Wang, Sanhu; Dong, Yongjun; Yang, Guoyu
Abstract: A Staphylococcus aureus ( S.aureus ) was isolated from pigs suffered in pneumonia that can't be cured by antibiotic such as methicillin and vancomycin. It was demonstrated that baicalin, an active natural compound extracted from the traditional Chinese medicinal, possess antimicrobial activity. In the present study, we evaluate it efficacy in vitro and vivo against this isolated methicillin-resistant S.aureus (MRSA). Our findings demonstrated that baicalin can inhibit S. aureus growth in a dose-dependent manner and attenuate the biofilm formation. Scanning electron microscopies showed that cell membrane was damaged and accompany with contents leaks after treated with high concentration of baicalin. In addition, baicalin exerted inhibitory effects on the expression of S.aureus virulence-related factors. Moreover, baicalin treated mice had enhanced survival after a lethal dose of S.aureus infection compared with untreated mice. Simultaneously, the pathological tissue damage and bacterium burden were decrease in baicalin treated mice. These data demonstrated that baicalin displayed a high effectiveness in vitro and vivo against MRSA infection, suggesting that baicalin may potentially be used to treat MRSA infection. Highlights: Baicalin inhibit S. aureus growth and attenuate the biofilm formation. Baicalin disrupt MRSA cell membrane. Baicalin inhibit the expression of virulence genes. Baicalin could improve the health status of infected animals.